WORKSHOP PERENCAAAN STRATEGIK (STRATEGIC PLAIN) SMU NEGERI SE PROPINSI DIY DALAM PENGEMBANGAN BROAD BASED EDUCATION - Wiyono, Giri; Sarbiran, Sarbiran (Universitas Negeri Yogyakarta, 2004)
The PPM FT UNY team shall implements the IPTEKS in actrvrty of Strategi Planning Worshop for focusing to problem sloving. The following problem points may appear on the school, namely : school wants information for conducting the shool needs analysis; and schoolwork program drawled up could require a strategic planning process which oriented for school needs in field of life skills.The purpose of this IPTEKS apllication program is to increase school headmaster ability for making the schoolwork program based a strategic planning process. Therefore headmasters of SMU have skills in areas : (1) The ability to conduct the school needs analysis; (2) The ability to formulate the school vision and mission; (3) The ability to draw up plans for school development; (4) The ability to perform SWOT analysis (internal and external condition); (5) The ability to formulate the school objective; (6) The ability to understand of the way to formulate strategy.Methods used in Strategic Planning Workshop are lecture, question-answer, demonstration, group task, seminar, guidance to make the schoolwork programs based a strategic planning process, and games in outbound training. Learning approaches used in this training are adult education and pratice.The result of Strategic Planning Workshop can be concludes as follows1. Participants have global vision in tehnology and strategic issues of education as formulation and development prpcess of the schoolwork programs for increasing quality of education in each school.2. Participants can formulate and develop the schoolwork programs based strategic planning process that oriented for school needs in field of life skills.3. Participants can develop self-power as headmasters who have the transformationalleadership for implement the schoolwork programs based strategic planning and can operational control this program integrated.Key words: strategic planning - life skill.